Analisis Efektivitas Sistem Pengendalian Internal dalam Upaya Meningkatkan Efisiensi Piutang Usaha - Hafidzussalam, Hafidzussalam; Rosmiati, Mia (Indonesian Accounting Literacy Journal, 2025)
Perusahaan Umum Daerah (Perumda) Air Minum Tirta XYZ has one phenomenon that has a low service assessment, a fluctuating percentage of accounts receivable, an increase in accounts receivable over the last five years, and the efficiency of receivable receipts that slightly reach the target every month. This study aims to determine the effectiveness of the internal control system in managing the efficiency of accounts receivable applied by the company through the COSO framework approach. The analysis will provide recommendations for companies in managing accounts receivable. The research method used is a qualitative descriptive method with a case study approach through data collection techniques through observation, interviews, and documentation. The results of the study based on the components of the internal control system obtained very adequate results for the control environment, the components of risk assessment, control activities, and information and communication were adequate, and monitoring activities with inadequate results.